2015
DOI: 10.1152/ajpheart.00451.2015
|View full text |Cite
|
Sign up to set email alerts
|

Chloride intracellular channel 4 is required for maturation of the cerebral collateral circulation

Abstract: Lucitti JL, Tarte NJ, Faber JE. Chloride intracellular channel 4 is required for maturation of the cerebral collateral circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…No additional decrease occurred at 18 months of age (~ 56 hye). Absence of effect at 1 month indicates that the presence of fewer and smaller collaterals is not due to decreased collaterogenesis, which occurs in the perinatal period and determines collateral number and diameter in the adult [ 25 28 ]. The latter could possibly have occurred secondary to parenchymal Aβ that has been detected in 1-month-old transgenic AD mice [ 45 ], or from non-specific effects of transgene insertion or private mutations/genetic drift in the AD strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No additional decrease occurred at 18 months of age (~ 56 hye). Absence of effect at 1 month indicates that the presence of fewer and smaller collaterals is not due to decreased collaterogenesis, which occurs in the perinatal period and determines collateral number and diameter in the adult [ 25 28 ]. The latter could possibly have occurred secondary to parenchymal Aβ that has been detected in 1-month-old transgenic AD mice [ 45 ], or from non-specific effects of transgene insertion or private mutations/genetic drift in the AD strains.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, collateral extent varies widely among individuals. In mice, pial collaterals form late during gestation and undergo perinatal maturation that determines their extent in the adult [ 25 28 ]. This collaterogenesis process varies widely due to differences in genetic background [ 23 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clic4 gene deficiency results in reduced expression of Vegfr2 , Vegfr1 , Vegfc , and mural cell markers associated with a reduction in ischemia-induced expression of hypoxia inducible factor-1α (HIF-1α)5). Recent work showed that overexpression of VEGF-A in Clic4 (-/-) mice rescued defects in collateral maturation by preventing mural cell loss and collateral pruning, thus restoring collateral number and diameter and reducing stroke severity in adults23). In fact, hCMEC/D3 showed high Clic4 mRNA and protein expression, whereas HUVEC did not (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…CLIC4 plays a role in the acidification of intracellular vacuoles that are required for tubulogenesis (Ulmasov et al, 2009). Clic4 -/mice exhibit aberrant collateral circulation in response to ischemic injury (Chalothorn, Zhang, Smith, Edwards, & Faber, 2009;Lucitti, Tarte, & Faber, 2015).…”
Section: Clic4mentioning
confidence: 99%